Emotional Intelligence as a Strategic Driver of Competitive Advantage and Service Quality in the Banking Industry - Chaudhary, Manoj Kumar; Neupane, Krishna; Dhungana, Madan; Giri, Bishnu (International Research Journal of MMC, 2024)
This research aims to determine whether emotional intelligence (EI), particularly in government-owned commercial banks, is a valid measure of service quality in the banking sector. The study aims to ascertain how emotional intelligence (EI) raises the caliber of services, with a particular emphasis on the departments of operations, credit, and customer service. Using a quantitative methodology, data were collected through purposive sampling from 284 employees in particular bank branches in Kathmandu. The findings show that emotional intelligence (EI) and service quality are highly correlated. Workers with higher EI are more adept at managing their emotions, positively relating to clients, and offering superior customer service. Self-awareness, social awareness, and relationship management are crucial in enhancing service quality, with relationship management exerting the most significant influence. The study's limited scope focusing only on government-owned banks in a particular area may restrict its applicability opening up new avenues for future studies on emotional intelligence in private banking and other sectors of the economy.